2011
DOI: 10.1016/j.cellimm.2011.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of macrophage plasticity in brown and white adipose tissue

Abstract: There are still questions about whether macrophage differentiation is predetermined or is induced in response to tissue microenvironments. C2D macrophage cells reside early in the macrophage lineage in vitro, but differentiate to a more mature phenotype after adoptive transfer to the peritoneal cavity (PEC-C2D). Since C2D macrophage cells also traffic to adipose tissue after adoptive transfer, we explored the impact of white adipose tissue (WAT), brown adipose tissue (BAT) and in vitro cultured adipocytes on C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…Prior studies have shown that macrophages isolated from murine BAT following adoptive transfer experiments have reduced expression of cytokine, chemokine, and receptor transcripts compared to their in vitro counterparts or those isolated from WAT [17]. Similarly, in the present study, white adipocytes induced expression of several inflammatory transcripts in macrophages, while brown adipocytes either reduced or did not significantly affect gene expression in both U937 and THP-1 macrophages regardless of stimulation state (Figures 3 and 4).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Prior studies have shown that macrophages isolated from murine BAT following adoptive transfer experiments have reduced expression of cytokine, chemokine, and receptor transcripts compared to their in vitro counterparts or those isolated from WAT [17]. Similarly, in the present study, white adipocytes induced expression of several inflammatory transcripts in macrophages, while brown adipocytes either reduced or did not significantly affect gene expression in both U937 and THP-1 macrophages regardless of stimulation state (Figures 3 and 4).…”
Section: Discussionsupporting
confidence: 65%
“…Of interest is that macrophage infiltration in BAT was found to be significantly less than that in WAT [16] and enhanced mRNA expression of inflammatory molecules, including tumor necrosis factor (TNF) α , interleukin-6 (IL-6), and monocyte chemotactic protein (MCP-1), was nearly 10–100-fold less in BAT than that in WAT in DIO mice. In addition, others have shown that expression of proinflammatory cytokines is lower in BAT than in WAT in normal mice [17] and expression of several cytokines has been found to be lower in C2D macrophage cells that were isolated after in vivo injection into BAT compared to injection into WAT [17]. However, as adipose tissue is a heterogeneous organ, it is unknown which specific type(s) of cell(s) in the adipose tissue environment is(are) contributing to the observed differences between WAT and BAT.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, preadipocytes inhibited the expression of galectin-3 by a specific subpopulation of macrophages, known as peritoneal-C2D macrophages, which retains plasticity in response to different microenvironments. Peritoneal-C2D macrophages that migrated to WAT expressed higher levels of galectin-3 than macrophages that moved to brown adipose tissue [93]. Moreover, in the course of monocyte-to-macrophage differentiation, galectin-3 mRNA and protein levels are substantially upregulated by M2 macrophages when compared with M1 macrophages [94].…”
Section: Adipose Tissue Inflammationmentioning
confidence: 99%
“…Cells were stained with carboxyfluorescein diacetate succinimidyl ester (CFDA-SE) according to the manufacturer’s protocol and as described before [4].…”
Section: Methodsmentioning
confidence: 99%
“…Because the adoptive transfer of C2D macrophages can ameliorate the impact of infection [22] and C2D macrophages trafficked to adipose tissue [4], we wondered if the cells would be able to influence the adipose tissue environment if they overexpressed IL-10. Therefore, we constructed a C2D macrophage cell line that stably overexpresses IL-10 (C2D-IL10).…”
Section: Introductionmentioning
confidence: 99%